Regulatory T cells in skin lesions and blood of patients with bullous pemphigoid. (18th January 2013) - Antiga, E.; Quaglino, P.; Volpi, W.; Pierini, I.; Del Bianco, E.; Bianchi, B.; Novelli, M.; Savoia, P.; Bernengo, M.G.; Fabbri, P.; Caproni, M.
Abstract Background Although regulatory T cells (Tregs) are affected in several autoimmune skin diseases, only two studies have been performed in patients with bullous pemphigoid (BP) with contrasting results. Objective To characterize Tregs and to determine the serum levels of regulatory cytokines in patients with BP. Methods In BP lesional skin, immunohistochemistry and confocal microscopy were performed for CD4+, CD25+, forkhead/winged helix transcription factor (FOXP3)+, transforming growth factor (TGF)‐β+ and interleukin (IL)‐10+ cells. In addition, the number of CD4+CD25++FOXP3+ Tregs in peripheral blood was assessed by flow cytometry, and the levels of TGF‐β and IL‐10 were determined in serum samples by enzyme‐linked immunosorbent assay before and after steroid therapy. Controls included patients with psoriasis, atopic dermatitis (AD) and healthy donors. Results The frequency of FOXP3+ cells was significantly reduced in skin lesions from patients with BP (P < 0.001) compared with psoriasis and AD. Moreover, the number of IL‐10+ cells was lower in BP than in psoriasis (P < 0.001) and AD (P = 0.002), while no differences were observed in the number of TGF‐β+ cells. CD4+CD25++FOXP3+ Treg in the peripheral blood of patients with BP was significantly reduced compared with healthy controls (P < 0.001), and augmented significantly after steroid therapy (P = 0.001). Finally, TGF‐β and IL‐10 serum levels were similar in patients with BP compared with healthy controls. However, after therapy, BP patients showed significantly higher IL‐10 serum levels than before therapy (P = 0.01). Conclusions These data suggest that the depletion of Tregs and of IL‐10 in patients with BP may be an important factor in the pathogenesis of the disease.